IMPROVING STUDENT'S VOCABULARY BY USING OUTDOOR ACTIVITIES AT THE SIXTH YEAR OF SD NEGERI 3 JEKANI MONDOKAN SRAGEN - SARI , JOHAR DIAH AYU PUSPITA (2010)
This research is intended to improve the students' vocabulary by using outdoor activity at the sixth year of SD Negeri 3 Jekani Mondokan Sragen. The objectives of this research are 1) to know whether or not the outdoor activity able to improve student's vocabulary 2) to describe the implementation of teaching vocabulary by using outdoor activities to improve student's vocabulary for the sixth year in SD Negeri 3 Jekani Mondokan Sragen 3) to describe the result of teaching vocabulary by using outdoor activities to improve student's vocabulary for the sixth year of SD Negeri 3 Jekani Mondokan Sragen 4) to know how far the improvement got by the students. In this research paper, the writer uses classroom action research. The data are field notes, interview script, and scores of pre-test and post-test. She applies an observation, interview, and document analysis to collect data. To analyze the data the writer uses a qualitative research is the reducing the data, displaying the achievement and monitoring students, and verifying the students score. The results of the research show that: 1) outdoor activities can increase student's vocabulary. It can be seen from the increasing result of each cycle. 2) In the process of improving student's vocabulary by using outdoor activity, the students tend to be active, enjoy and have motivation in learning English. 3) They also memorize vocabulary well and their vocabulary is enriched. 4) the improvement got by the students is 23, 13.